TRANSNATIONALISM THREAT TO THE INDONESIAN SOCIETY IN THE BORDER AREA OF INDONESIA-MALAYSIA (STUDY ON CAMAR BULAN SOCIETY) - Sulistyarini Sulistyarini; Jagad Aditya Dewantara; Shilmy Purnama; Edwin Mirzachaerulsyah (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
In general, issues related to the threat of transnationalism at the border have long been a hot topic among academics. This issue includes a real threat that threatens the nationalism of people living on the border. The purpose of this research is to prove transnationalism from the real life of the people who live on the border of the hamlet of Camar Bulan Temajuk. The use of ethnographic methods deepens the analysis of data in the field in the form of descriptive and objective data taken from 12 informants from different community groups. Field data collection begins with observations and interviews with community informants. The result The data describes various threats and obstacles that come from military threats at the border. However, non-military threats such as the circulation of foreign money, kinship ties, infrastructure, social inequalities, and overly free community interactions have made the psychology of society towards Indonesian nationalism lose and fade. Furthermore, transnationalism also disappears the people's national identity at the border, prides themselves on being Indonesian citizens, and more trust in other countries. This research provides contributions and thoughts related to the real threat of transnationalism to be reference material and evaluation for academics, government, and field practitioners.